A CONTINUOUS REVIEW INVENTORY MODEL WITH COLLECTING USED PRODUCTS CONSIDERATION - Chen, Cheng Kang; ’Ulya, M. Akmalul (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Recently, owing to growing environmental concerns, the activities of collecting used products for remanufacturing or recycling has attracted a great deal of attention from academic and industrial communities. In this paper, we extend the classical continuous review inventory system to consider the activities of collecting used products. In the basic model, assuming the lead time demand follows normal distribution, we seek to minimize total cost per unit time through determining the order quantity, the reorder point and return rate. Also, we investigate the case when the distribution of lead time demand is unknown and only mean and variance of lead time demand are known. An iterative search algorithm is developed to find the optimal solution. Several numerical examples are provided to illustrate the features of our proposed models. Recently, owing to growing environmental concerns, the activities of collecting used products for remanufacturing or recycling has attracted a great deal of attention from academic and industrial communities. In this paper, we extend the classical continuous review inventory system to consider the activities of collecting used products. In the basic model, assuming the lead time demand follows normal distribution, we seek to minimize total cost per unit time through determining the order quantity, the reorder point and return rate. Also, we investigate the case when the distribution of lead time demand is unknown and only mean and variance of lead time demand are known. An iterative search algorithm is developed to find the optimal solution. Several numerical examples are provided to illustrate the features of our proposed models. Keywords: inventory, return rate, distribution free.